Meningkatkan Partisipasi Politik Perempuan dalam PILGUB Jawa Tengah 2018 - Wenny Eka Septina; Erisandi Arditama (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
Political education is essential to do, as advanced democracy depends on high or low. political participationWomen having a share is the important thing for development, including in politics.Role of women in developing a nation, because she is the first school for her children. In politics, gait and participation of women had not yet it is significant.Women still object to complement to scoop sound .On the other side , there are still many women who are still with low levels of education also influences political participation, it would result in the apathy so high. Added the sosio-kultural villagers still characterless patriarkhi by stressing superiorias. men against women Based on this condition, political education for women on the subject to prevent in the form of a political apathy golput and increasing political participation in the democracy.